MAINTAINING TRADITIONS AMID DISRUPTION: THE PHENOMENON OF VIRTUAL AUTONOMY IN HINDU CULTURE AND RELIGION - I Made Widiantara (JKKB: Jurnal Kajian Komunikasi Budaya (JCCS: Journal of Cultural Communication Studies), 2024)
The COVID-19 pandemic has brought significant changes to the implementation of religious ceremonies worldwide, including the otonan ceremony, an important birthday celebration in Balinese Hindu culture. This study explores the adaptation and transformation of the otonan ceremony in the context of the pandemic, with a specific focus on the utilization of virtual technology. The research aims to investigate the impact of COVID-19 on the implementation of the otonan ceremony, the ways in which the Balinese Hindu community adapts and utilizes virtual technology to conduct the ceremony, the preservation of spiritual meaning and values in virtual settings, and the reflection of cultural and religious resilience in the face of disruption. The study employs a qualitative approach with a case study method, involving in-depth interviews with Balinese Hindu practitioners and religious leaders. The theoretical framework draws upon concepts of cultural resilience, digital culture, ritual theory, and the integration of technology in religious practices. The findings reveal that the Balinese Hindu community has successfully adapted to the challenges posed by the pandemic by conducting otonan ceremonies virtually, using video call applications such as WhatsApp and Zoom. The spiritual meaning, values, and essence of the ceremony are maintained through sincere intentions, active participation, ritual adaptations, and the use of sacred symbols. The phenomenon of virtual otonan reflects the resilience and adaptability of Balinese Hindu culture and religion in navigating the disruptions caused by the pandemic while preserving the core spiritual elements of the ceremony. This study contributes to the understanding of cultural and religious transformation in the digital era and offers valuable insights into the role of technology in sustaining and adapting religious traditions during times of crisis. The findings highlight the importance of cultural resilience and the innovative ways in which communities maintain their religious practices in the face of adversity